Quantification of Aging-Related Decreases in Sensory Innervation of the Bladder Trigone in Rats - Rijk, Mathijs M. de; Peter, Saša; Wolf-Johnston, Amanda; Heesakkers, John; Koeveringe, Gommert A. van; Birder, Lori A. (International neurourology journal, 2024)
Purpose: The prevalence of lower urinary tract symptoms (LUTS), characterized by problems regarding storage and/or voiding of urine, is known to significantly increase with age. Effective communication between the lower urinary tract and the central nervous system (CNS) is essential for the optimal function of this system, and heavily relies on the efficient interaction between the bladder urothelium and the afferent nerve fibers situated in close proximity to the urothelium within the lamina propria.Methods: We aimed to quantify aging-related differences in the expression of calcitonin gene-related peptide (CGRP, an established marker for sensory nerve fibers) in the trigonal mucosal layers of young (3–4 months) and aged (25–30 months) rats. We evaluated trigonal tissue from 3 animals per age group. Tissue was serially sectioned at 10 μm and stained for CGRP. Images were taken along the full length of the tissue. For each image we computed the total CGRP-positive area (μm2) and the median value for each animal was used for further analysis.Results: Upon statistical analysis the aged rats show a significantly lower CGRP-positive area compared to young rats (P=0.0049). These results indicate that aging has a negative effect on the area of CGRP-positive signal in the trigone.Conclusions: The structural and functional integrity of the sensory web in the trigonum of rats is negatively affected by the aging process, potentially leading to impaired communication between the bladder urothelium the CNS. Consequently, these perturbations in the sensory system may contribute to the pathogenesis or exacerbation LUTS.